2021
DOI: 10.17645/up.v6i2.3790
|View full text |Cite
|
Sign up to set email alerts
|

The Negotiation of Space and Rights: Suburban Planning with Diversity

Abstract: The increasing suburbanization of immigrant settlement in Canada’s major receiving cities has created unprecedented challenges for municipalities. Despite emerging research about the rise of ethnic suburbs in Canada and abroad, the role of suburban municipalities in facilitating immigrant integration and planning with diversity remains unclear. Based on mixed-method ethnographic research, this article investigates how immigrant and racialized communities in the Greater Toronto Area have significantly transform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Zhuang (2017) observed such third places at many trades and businesses be they private (barbershops, cafés or restaurants) or public (shopping plazas and public spaces). These third places further extend the functionality of ethnic shopping clusters towards community-building and promoting social interactions (Zhuang, 2021). Zhuang (2021, p.119) also found that a third of the visitors to ethnic retail clusters visit them for social reasons not shopping and that 95 % of the visitors feel 'at home'; thus, Chinese and South Asian communities have transformed the spaces to locus of new meanings and identities.…”
Section: Whose City?mentioning
confidence: 95%
“…Zhuang (2017) observed such third places at many trades and businesses be they private (barbershops, cafés or restaurants) or public (shopping plazas and public spaces). These third places further extend the functionality of ethnic shopping clusters towards community-building and promoting social interactions (Zhuang, 2021). Zhuang (2021, p.119) also found that a third of the visitors to ethnic retail clusters visit them for social reasons not shopping and that 95 % of the visitors feel 'at home'; thus, Chinese and South Asian communities have transformed the spaces to locus of new meanings and identities.…”
Section: Whose City?mentioning
confidence: 95%
“…Planners and those responsible for training planners must consider more efficient ways of engaging with racialized communities. Without proper community consultation, these inequities of accessibility can become further accentuated (Zhuang, 2021). Conversations must consider the lived experiences of individuals and incorporate that knowledge into consultation and subsequent decisions (Zhuang, 2021).…”
Section: Relationship Buildingmentioning
confidence: 99%
“…These groups understand the needs and desires of the community and hold the ability to reach and advertise the initiatives (Ramakrishnan & Viramontes, 2010). NIAs tend to have a high proportion of grassroots groups (Bhatia, 2020) Without proper community consultation, the inequities of accessibility can become further accentuated (Zhuang, 2021). Planners and those responsible for training planners must consider more efficient ways of engaging with racialized communities (Zhuang, 2021).…”
Section: Relationship Buildingmentioning
confidence: 99%
See 2 more Smart Citations